Evaluation of hybrid rye on growth performance, carcass traits, and efficiency of net energy utilization in finishing steers. Issue 3 (12th September 2020) - Rusche, Warren C; Walker, Julie Ann; Sexton, Peter; Brattain, Rebecca S; Smith, Zachary K
Abstract: Crossbred beef steers with a high percentage of Angus ancestry [ n = 240, initial shrunk body weight (BW), 404 ± 18.5 kg] were used in a 117-d feedlot experiment to evaluate the effect of hybrid rye (Rye; KWS Cereals USA, LLC, Champaign, IL) as a replacement for dry-rolled corn (DRC) on growth performance, carcass traits, and comparative net energy (NE) value in diets fed to finishing steers. Rye from a single hybrid (KWS Bono) with an ergot alkaloid concentration of 392 ppb was processed with a roller mill to a processing index (PI) of 78.8 ± 2.29. Four treatments were used in a completely randomized design ( n = 6 pens/treatment; 10 steers/pen), where DRC (PI = 86.9 ± 4.19) was replaced by varying proportions of Rye [DRC:Rye, dry matter (DM) basis (60:0), (40:20), (20:40), and (0:60)]. Liver abscess scores and carcass characteristics were collected at the abattoir. Carcass-adjusted performance was calculated from hot carcass weight (HCW)/0.625. Performance-adjusted NE was calculated using carcass-adjusted average daily gain (ADG), DM intake (DMI), and mean equivalent shrunk BW with the comparative NE values for rye calculated using the replacement technique. Data were analyzed using the GLIMMIX procedure of SAS 9.4 (SAS Inst. Inc., Cary, NC) with pen as the experimental unit. Treatment effects were tested using linear and quadratic contrasts, as well as between diets with and without Rye. Replacing DRC with Rye linearly decreased ( P ≤ 0.01) carcass-adjusted final BW, ADG, DMI, and gain:feed (G:F). Feeding rye linearly decreased HCW and longissimus muscle area ( P ≤ 0.04). Distributions of liver scores and USDA grades for quality and yield were unaffected by treatment ( P ≥ 0.09). Estimated replacement NE for maintenance (NEm) and gain (NEg) values for rye, when included at 60% of diet DM, were 1.90 and 1.25 Mcal/kg, respectively. Rye can be a suitable feed ingredient in finishing diets for feedlot steers. Estimated replacement values of Rye when fed at 60% of diet DM closely agreed with current tabular standards but, when included at 20% of diet DM, estimated NEm and NEg values of Rye were increased 9.5% and 12.8%, respectively. Net energy value of Rye for gain is approximately 84% compared to DRC; thus, the complete replacement of DRC with Rye depressed DMI, ADG, G:F, and carcass weight.